Usulan Peningkatan Efektivitas Mesin Multi Bor dengan Menggunakan Metode Overall Resource Effectiveness dan Failure Mode Effect Analysis - Sanjaya, Wahyu Eka Putra; Garside, Annisa Kesy; Wardana, Rahmad Wisnu; Sanjaya , Wahyu Eka Putra; Wardana , Rahmad Wisnu (Universitas Katolik Parahyangan, 2024)
PT XYZ is a company engaged in the wood industry which is marketed for export. In carrying out the production process losses often occur in multi drill machines thereby reducing the effectiveness of the machine. These losses arise because the machine is often adjusted and experiences breakdowns. Therefore, this study will analyze the effectiveness of the multi drill machine using the Overall Resource Effectiveness (ORE) method. Furthermore, fishbone diagrams, Failure Mode Effect Analysis (FMEA), and Total Productive Maintenance will be used as a method for providing improvement suggestions to increase machine effectiveness. From the calculation results, the ORE value is 59.58% (below the standard, which is 85%). Furthermore, by using the fishbone and FMEA methods, 3 failure modes with the largest RPN values were taken. Proposed improvements to increase the effectiveness of multi-bore machines are the application of autonomous maintenance, quality maintenance, preventive maintenance, and provision of safety stock.